Capital Assets Analysis Pricing Model as a Basis for Investment Decisions Investment in Shares of PT Mustika Ratu and PT Multi Indocitra Listed on the IDX Period 2022 - Dika Chandra Laili; Rosa Devina; Khansa Tsabita; Maria Yovita R.Pandin (International Journal of Economics and Management Research, 2024)
In investing, prospective investors' astuteness in exploring and processing information will be used as a decision-making tool for investing which will determine how much risk and profit they will obtain in the future. This research aims to determine the magnitude of profits and risks and classify efficient and inefficient shares by applying the Capital Asset Pricing Model method to cosmetics sub-sector companies listed on the IDX. The method used in the research is a qualitative method with quantitative data, in the form of a list of the latest stock prices, interest rates, and the Indonesian Sharia Stock Index sourced from the official website of the Indonesian Stock Exchange, Yahoo Finance, and Bank Indonesia.